2019
DOI: 10.3396/ijic.v15i1.002.19
|View full text |Cite
|
Sign up to set email alerts
|

Prospective surveillance of hospital associated infections epidemiology in a haematology-oncology department

Abstract: In haematology-oncology, intensified procedures have been associated with higher risk of healthcare associated infections (HAIs).This study aimed to estimate the incidence and to identify risk factors of HAIs in a haematology-oncology unit in a Tunisian university hospital. We conducted a prospective study, during 06 months from Mars through September 2016 in the department of hematology- oncology in a tertiary teaching hospital in Tunisia. Patients, admitted for ≥48 h, were followed until hospital discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Blood cultures are positive in about 20% and 30% of cases in Hughes et al and Lyman and Rolston studies [45], [46]. Meidani et al in Iran performed their study on neutropenic patients with fever, they found 68.4% of medical documents with no result for culture of any body fluid and only 2.6% of patients had positive blood culture [47], and this is consistent with the results of Bouafia et al study in which the percentage was slightly lower (24.1%) [48].…”
Section: Discussionsupporting
confidence: 72%
“…Blood cultures are positive in about 20% and 30% of cases in Hughes et al and Lyman and Rolston studies [45], [46]. Meidani et al in Iran performed their study on neutropenic patients with fever, they found 68.4% of medical documents with no result for culture of any body fluid and only 2.6% of patients had positive blood culture [47], and this is consistent with the results of Bouafia et al study in which the percentage was slightly lower (24.1%) [48].…”
Section: Discussionsupporting
confidence: 72%